مسؤولية البنك المركزي في مواجهة خطر التعثر المالي للبنوك و المؤسسات المالية - Ait Ouazzou, Zaina (جامعة الوادي University of Eloued, 2019)
ملخص: يعتلي البنك المركزي هرم النظام المصرفي في الدولة، فهو بنك البنوك، يشرف على توجيهها ورقابتها. أنيط البنك المركزي بمهمة الحفاظ على الاستقرار المالي والنقدي في الدولة، فهو المسؤول على إصدار النقد ومراقبة التضخم، وذلك في إطار السياسة الاقتصادية العامة للدولة. ومن الأهداف الأساسية لهذه المؤسسة السهر على السير الحسن والمستقر لكل المعاملات المصرفية والمالية التي تقوم بها البنوك والمؤسسات المالية حيث تقع عليها مسؤولية الحفاظ على الاستقرار المالي لهذه المؤسسات وحمايتها من خطر التعثر المالي. لكن، هل تمتد هذه المسؤولية إلى كل حالات التعثر المالي الذي تتعرض له البنوك والمؤسسات المالية وأيا كانت أسبابه؟ Abstract: The Central Bank represents the keystone of banking and financial system of the State. The Central Bank is on the top of this system. This institution works for the national economic policy and its purpose is to maintain the financial and monetary balance. However, the two main roles of this institution are: to print the money, and to ensure its value both on the internal and external levels. With these two preponderant roles, the Central Bank aims to ensure the progress of all financial or banking operations undertaken by financial institutions and banks. But, does this responsibility extend to all the financial failures that these banking and financial actors can face, whatever their causes?
La Responsabilité De La Banque Centrale Face Au Risque De La Défaillance Financière Des Banques Et Des Institutions Financières
Keywords: البنك المركزي ; النظام المصرفي ; الرقابة المصرفية ; التعثر المالي ; البنوك ; المؤسسات المالية ; الأخطار المصرفية; The Central Bank; banking and financial system; responsibility ; financial failures ; the bank